2022
DOI: 10.1186/s12889-022-14724-2
|View full text |Cite
|
Sign up to set email alerts
|

Trends in prevalence of overweight and obesity among South African and European adolescents: a comparative outlook

Abstract: Background South Africa has several national surveys with body weight-related data, but they are not conducted regularly. Hence, data on longitudinal trends and the recent prevalence of adolescent obesity are not readily available for both national and international reporting and use. This study collectively analysed nationally representative surveys over nearly 2 decades to investigate trends in prevalence of adolescent obesity in South Africa. Furthermore, it compared these data with similar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 27 publications
2
3
0
Order By: Relevance
“…Furthermore, our results are consistent with previous studies from other African countries [37,38]. Sex differences in overweight and obesity have also been reported in other countries where biology, physical activity levels, and socio-cultural beliefs contribute to these differences [39][40][41][42]. However, to the best of our knowledge, our paper is the first one to link low obesity awareness and overweight/obesity prevalence, both of which are more pronounced in girls in Harare.…”
Section: Prevalence Of Overweight/obesity and Low Obesity Awarenesssupporting
confidence: 92%
“…Furthermore, our results are consistent with previous studies from other African countries [37,38]. Sex differences in overweight and obesity have also been reported in other countries where biology, physical activity levels, and socio-cultural beliefs contribute to these differences [39][40][41][42]. However, to the best of our knowledge, our paper is the first one to link low obesity awareness and overweight/obesity prevalence, both of which are more pronounced in girls in Harare.…”
Section: Prevalence Of Overweight/obesity and Low Obesity Awarenesssupporting
confidence: 92%
“…Based on healthcare data, the worldwide prevalence of obesity has nearly tripled since 1975 with an estimated 135 million people being overweight or obese in Europe [ 2 ]. However, the ratio of overweight or obesity shows a high variability according to the different geographical region, such as 42.2% in the general adult population in the United States [ 3 ]; 44.8% among the Latin population in the United States [ 3 ]; 17.8% in the overall population in Dubai [ 4 ]; 21.6% in South African subjects [ 5 ] and 47.6% in Europe [ 6 ]. As a matter of fact, data from Central Eastern European region are more concerning than those from Western European countries; for instance, in the Hungarian population, the overweight (body mass index; BMI: ≥25 kg/m 2 ) and obesity (BMI: ≥30 kg/m 2 ) prevalence are approximately 35% and 20%, respectively [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, studies conducted in Africa confirmed that the relationship between socio-economic status and adolescent obesity is positive and that adolescents from the highest SES households had a greater chance of being obese then those from lower SES households. They posited that an increase in wealth increases the availability of unhealthy food [34,48]. However, this study found that the level of a mother's education has a significantly negative relationship with obesity of female adolescents, and it can be said that the situation is the same as in other developed countries.…”
Section: Discussionmentioning
confidence: 57%
“…Regarding African countries, it should be mentioned that over the years, overweight and obesity have increased. From 1998 to 2016, the trend toward overweight and obesity in female adolescents increased from 26.77% to 33.88%, respectively [34]. Additionally, a recent publication, which, among other things, calculated obesity prevalence assessment based on the value of BMI, provides an accurate picture of the level of nutrition in a sample of adolescents aged 15 and over in 35 European countries, including the 27 European Union (EU) Member States, 5 EU candidate countries, and 3 countries located in the European Free Trade Association (EFTA).…”
Section: Discussionmentioning
confidence: 99%